Atypia in pulmonary cytology: Morphologic spectrum and causes. Issue 4 (20th November 2021) - Layfield, Lester J.; Baloch, Zubair
Abstract: Background: The term "atypical" has had a long history of usage in cytology but has had variable definitions and usage. Most commonly the term was used to indicate a degree of cytomorphologic abnormality greater than that clearly due to reactive or reparative changes but not associated with a high concern on the part of the cytopathologist that a malignancy is present. The Papanicolaou Society of Cytopathology System for Reporting Respiratory Cytology provided a foundation for using the category "Atypical" along with the category "Suspicious for Malignancy" to categorize the spectrum of morphologic changes ranging from those which are clearly benign to those that are clearly malignant. The two intermediate categories of "Atypical" and "Suspicious for Malignancy" have characteristic recommendations resulting in clinical utility for both categories. Conclusion: The Papanicolaou Society of Cytopathology System for Reporting Respiratory Cytology represents a useful system with defined intermediate categories of Atypical and Suspicious for Malignancy.